Correlation between blood volume, culture sets, and detection rates in bloodstream infections - Katoch, Poonam; Kaur, Navjot; Gill, Parminder Kaur; Danish, M. D. (International Journal of Research in Medical Sciences, 2026)
Background: Blood culture remains the gold standard for diagnosing bloodstream infections (BSIs), with diagnostic yield influenced by variables such as blood volume, number of culture sets, and processing time. This study evaluates these factors and their impact on blood culture positivity rates using the BD BACTEC™ FX 40 system. Methods: A cross-sectional prospective study (June–December 2024) analysed blood cultures using BD BACTEC™ FX 40, assessing volume, sets, time to positivity (TTP), and organisms from laboratory records via standard microbiological methods. Results: A total of 2,016 blood cultures were processed, yielding an overall positivity rate of 28.67%. Cultures with adequate blood volume (≥8 ml per bottle) demonstrated significantly higher positivity rates compared to those with suboptimal volumes (p<0.05). The majority of cultures (59.5%) had a volume between 10-15 ml, which also corresponded to the highest proportion of early time to positivity (TTP <24 hours). Use of two or more culture sets notably increased detection rates. Gram-positive organisms were the predominant isolates, accounting for 48.79% of positive cultures, with Staphylococcus spp. being the most commonly identified. Turnaround time (TAT) for final reporting varied, with the highest proportion of positive cultures (30.97%) finalized within 24-48 hours. Conclusions: Adequate blood volume and multiple culture set significantly improve diagnostic yield in blood culture testing. Timely processing and reporting are crucial for effective clinical management of BSIs. These findings underscore the importance of adherence to recommended guidelines for blood culture collection and processing.